POTENSI LAHAN TANAMAN SAYURAN DI DANAU ALANI DESA BUKO KECAMATAN BUKO SELATAN KABUPATEN BANGGAI KEPULAUAN - Pokoti, Fitriani; Yatim, Herwin; Katili, Hidayat Arismunandar; Sariani, Sariani (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2023)
This study aims to determine the potential of vegetable crops in Lake Alani, Buko Village, South Buko District, Banggai Islands Regency and recommend the distribution of directions for the development of vegetable crops in Lake Alani, Banggai Islands Regency. This research will be carried out in Lake Alani and its surroundings located in Buko Village, South Buko District, Banggai Islands Regency. This research will be conducted in March - May 2023. Research is conducted in qualitative form to identify the quality and characteristics of land as parameters. Data on the quality and characteristics of the land are then compared (matching) with the criteria of land suitability classes that have been prepared based on the requirements for use or growing needs of Lettuce (Lactuca sativa) and Eggplant (Solanum melongena), where in the results of plant criteria obtained the actual land suitability class at the research site on Lettuce (Lactuca sativa) and Eggplant (Solanum melongena) classified as class (S3 = marginal), then by increasing improvement efforts obtained potential land suitability classes in lettuce and eggIn general, both types of vegetable crops namely Lettuce (Lactuca sativa) and Eggplant (Solanum melongena) can be developed for cultivation at the research site in Lake Alani, Buko Village, South Buko District, Banggai Islands Regency, by carrying out land processing such as liming or adding organic matter and fertilization plant crops are classified (S2 = moderately appropriate) in the development of vegetable crops.